SISTEM KEAMANAN BUKA PINTU OTOMATIS MENGGUNAKAN IDENTIFIKASI WAJAH BERBASIS MIKROKONTROLER ESP32 - Ari Prasetio; Asep Wasid (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2026)
In this modern era, security systems have become one of the most essential aspects of daily life, especially in homesecurity. The increasing rate of crime, which continues to rise along with technological advancements, makes itnecessary to implement reliable security systems to protect personal assets and privacy. To enhance home securitymore effectively, an Automatic Door Security System Using Face Recognition Based on an ESP32-CAMMicrocontroller was developed. This system allows homeowners to feel safer without constant concern about theirhome’s security. The system uses the ESP32-CAM microcontroller as its main controller, combined with a solenoiddoor lock module and a web browser interface. These components work together to detect and register faces thatare either newly enrolled or already stored in the system. When a registered face is successfully recognized, thedevice displays a green notification and automatically unlocks the door through the solenoid lock mechanism.Additionally, the captured facial data is processed and stored by the ESP32-CAM for future recognition